150k views
1 vote
Marlena solved the equation 2x + 5 = –10 – x. Her steps are shown below.

2x + 5 = –10 – x

3x + 5 = –10
3x = –15
x = –5
Use the drop-down menus to justify Marlena’s work in each step of the process.

User Kaleissin
by
5.5k points

2 Answers

3 votes

Answer:

Marlena is CORRECT

Explanation:

First step: add x on both sides.

you now have 3x + 5 = –10

Second step: subract -5 on both sides to isolate the variable term

you now have 3x = –15


Final step: divide 3 on both sides to isolate x

you now have x = –5

So x = -5

--------------------------------------------------

We can check our answer by plugging in -5 where ever you see x

2(-5) + 5 = –10 – (-5)

-10 + 5 = -10 + 5

-5 = -5

Since the equation is true, Marlena did solved the problem correctly

User Tomarto
by
5.4k points
7 votes

Answer:

step 1: addition property of equality

step 2: subtraction property of equality

step 3: division property of equality

Explanation:

(These are the CORRECT ANSWERS to Edge unlike the other ppl answers)

User Chris Pfohl
by
6.0k points